LATEX APPLICATION TRAINING FOR THESIS WRITING: A COMMUNITY SERVICE INITIATIVE FOR DEIYAI DORMITORY STUDENTS IN JAYAPURA, PAPUA - Agustinus Giai; Mickael Ruben Kaiway; Joni Joni; Pither Palamba; Selyus Rantepulung; Vhalentio Pakombong (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study describes a community service initiative for undergraduate students at the Deiyai Dormitory in Jayapura, Papua, that aims to improve academic writing skills through LaTeX training. A one-day intensive training program utilizing a practice-based technique was attended by 26 individuals who had never used LaTeX before. Document structure, mathematical formatting, figures and tables, cross-references, and BibTeX were all covered in the training materials. 100% of participants successfully produced simple LaTeX documents, surpassing the 80% goal (+20%), according to the results. However, only over 30% were proficient in creating thesis templates and BibTeX, falling short of the expectations of 60% (−30%) and 70% (−40%). The goal of ≥40 (−35%) was not met by participation (26). In terms of access, the dual-platform concept was validated by the fact that 38% utilized computers and 62% used smartphones via Overleaf. Two completed assignments (goal ≥5) and a learning community with more than thirty participants and more than ten talks over a three-month period were among the post-training outcomes. These findings show a significant short-term increase in fundamental skills, but they also demonstrate the need for continuous interventions and long-term training for advanced competencies.